Neuroprotective effect of Orostachys spinose dry extract in cholinergic insufficiency - Ya. G. Razuvaeva; A. A. Toropova; E. A. Bayandueva; I. G. Nikolaeva (Acta Biomedica Scientifica)
Background. Orostachys spinosa (L.) Sweet. – a perennial plant of a wide habitat and contains various metabolites (amino acids, flavonoids, polysaccharides, etc.). Extracts from the aerial part of the plant are used in traditional medicine as an anticonvulsant and sedative.The aim of the work. To study the neuroprotective effect of O. spinosa in cholinergic deficiency.Materials and methods. The studies were carried out on 52 Wistar rats. The animals were administered scopolamine (1 mg/kg) daily for 21 days, followed by O. spinosa dry extract per os at a dose of 100 mg/kg for 14 days. On the day 32, the animals developed a conditioned passive avoidance reflex (CPAR), the integrity of which was checked after 1, 24 and 72 hours; on the day 35 they were tested in an “open field”. On the day 36, biochemical and histological studies of the brain were carried out.Results. It has been established that O. spinosa, against the background of scopolamine intoxication, reduces the anxiety of animals, stimulates exploratory activity in the open field test, improves the production and preservation of the CPAR, and also reduces the number of functionally inactive neurons (pyknotic and shadow cells) in the cerebral cortex. The extract reduces the lactate/pyruvate ratio by 47 %, intensifies the activity of mitochondrial complexes I and II by 54–64 %, and increases the concentration of adenosine triphosphate by 1.6 times compared to the control. O. spinosa exhibits antioxidant properties by reducing malondialdehyde and increasing the activity of catalase, glutathione peroxidase and glutathione reductase in the brain.Conclusion. O. spinosa dry extract has a neuroprotective effect in cholinergic deficiency. The studied extract exhibits antioxidant properties and stimulates energy processes in the brain